Hubungan Pengetahuan dan Sikap dengan Perilaku Konsumsi Fast Food Siswa SMA Negeri 2 Tuban: The Relationship between Knowledge and Attitudes with Student’s Fast Food Consumption Behavior in Senior High School 2 Tuban - Septi Eni Susanti; Veni Indrawati (UNIVERSITAS NGUDI WALUYO, 2023)
Fast food was food that contain high energy and fat, and low fiber. Excessive consumption of fast food could lead obesity. According to the Riskesdas’ data 2013 the prevalence of obesity due to consumption of fast food was 10,8% . Fast food consumption behavior affected by several factors included knowledge and attitudes. The main purpose of this research was to analyse the relationship between knowledge and attitudes with students’ fast food consumption behavior in senior high school 2 Tuban. The design of this research was cross sectional study to found the relationship between variables knowledge and attitudes with fast food consumption behavior. The respondents of this research was 240 students of senior high school 2 Tuban. Data analysis in this research used the Spearman correlation test. The result showed that there was a correlation between knowledge with students’ fast food consumption behavior. and there was a correlation between attitudes with students’ fast food consumption behavior. Therefore, it could be conclude that there was relationship between knowledge and attitudes with students’ fast food consumption behavior in senior high school 2 Tuban. ABSTRAK Fast food merupakan makanan yang mengandung tinggi energy, tinggi lemak, dan rendah serat. Perilaku konsumsi fast food berlebih menjadi salah satu penyebab terjadinya obesitas. Menurut data Riskesdas tahun 2013 prevalensi status gizi lebih akibat konsumsi fast food pada remaja di Indonesia sebesar 10,8%. Perilaku konsumsi fast food dipengaruhi oleh beberapa faktor diantaranya adalah pengetahuan dan sikap. Penelitian ini bertujuan untuk mengetrahui hubungan pengetahuan dan sikap dengan perilaku konsumsi fast food siswa SMA Negeri 2 Tuban. Desain dari penelitian ini adalah cross sectional study yang mencari hubungan antar variabel yaitu pengetahuan dan sikap dengan perilaku konsumsi fast food. Responden pada penelitian ini berjumlah 240 siswa SMA Negeri 2 Tuban. Analisis data pada penelitian ini menggunakan uji korelasi spearman dengan teknik pengambilan sampel menggunakan stratified random sampling. Hasil penelitian ini menunjukkan bahwa terdapat hubungan pengetahuan dengan perilaku konsumsi fast food siswa dan terdapat hubungan antara sikap dengan perilaku konsumsi fast food siswa. Dengan demikian dapat disimpulkan bahwa terdapat hubungan pengetahuan dan sikap dengan perilaku konsumsi fast food siswa SMA Negeri 2 Tuban.